A Case Study of 3D Scanning Techniques in Civil Engineering Using the Terrestrial Laser Scanning Technique - Artur Piekarczuk; Aleksandra Mazurek; Jacek Szer; Iwona Szer (Buildings)
This paper reviews the measurement challenges associated with 3D scanning techniques in civil engineering, exploring the practical aspects of scanning buildings and complex surfaces through various case studies. The paper details the conventional use of Terrestrial Laser Scanning (TLS) for reconstructing the technical documentation of a hall. Then it describes an unconventional application of this technique for measuring an External Thermal Insulation Composite System (ETICS) wall, aimed at detecting microdeformations caused by environmental factors controlled within a climatic chamber. Subsequently, the measurements of the insulated wall were repeated using a metrological grade laser scanner. The numerical data were analysed with inspection engineering methods. The deformation maps and displacements of selected reference points were compared. This approach yielded qualitative and quantitative results. The qualitative results, i.e., the distribution of deformations in the form of a map, turned out to be consistent. However, quantitative results show a significant discrepancy in extreme cases of up to 70%.